Four-factor prothrombin complex concentrate in adjunct to whole blood in trauma-related hemorrhage: Does whole blood replace the need for factors?. Issue 1 (10th July 2021) - Khurrum, Muhammad; Ditillo, Michael; Obaid, Omar; Anand, Tanya; Nelson, Adam; Chehab, Mohamad; Kitts, Daniel James; Douglas, Molly; Bible, Letitia; Joseph, Bellal
Abstract : BACKGROUND: The use of whole blood (WB) for the treatment of hemorrhagic shock and coagulopathy is increasing in civilian trauma patients. Four-factor prothrombin complex concentrate (4-PCC) in adjunct to component therapy showed improved outcomes in trauma patients. Our study aims to evaluate the outcomes of trauma patients who received 4-PCC and WB (4-PCC–WB) compared with WB alone. METHODS: We performed a 3-year (2015–2017) analysis of the American College of Surgeons—Trauma Quality Improvement Program database. All adult (age, ≥18 years) trauma patients who received WB were included. We excluded patients who were on preinjury anticoagulants. Patients were stratified into two groups, 4-PCC–WB versus WB alone, and matched in a 1:2 ratio using propensity score matching. Outcome measures were packed red blood cells, plasma, platelets, and cryoprecipitate transfused, in-hospital complications, hospital and intensive care unit (ICU) length of stay (LOS) among survivors, and mortality. RESULTS: A total of 252 patients (4-PCC–WB, 84; WB alone, 168) were matched. The mean ± SD age was 47 ± 21 years, 63% were males, median Injury Severity Score was 30 (21–40), and 87% had blunt injuries. Patients who received 4-PCC–WB had decreased requirement for packed red blood cell (8 U vs. 10 U, p = 0.04) and fresh frozen plasma (6 U vs. 8 U, p = 0.01) transfusion, lower rates of acute kidney injury ( p = 0.03), and ICU LOS (5 days vs. 8 days, p = 0.01) compared with WB alone. There was no difference in the platelet transfusion ( p = 0.19), cryoprecipitate transfusion ( p = 0.37), hospital LOS ( p = 0.72), and in-hospital mortality ( p = 0.72) between the two groups. CONCLUSION: Our study demonstrates that the use of 4-PCC as an adjunct to WB is associated with a reduction in transfusion requirements and ICU LOS compared with WB alone in the resuscitation of trauma patients. Further studies are required to evaluate the role of PCC with WB in the resuscitation of trauma patients. LEVEL OF EVIDENCE: Therapeutic, level III.